2022
DOI: 10.12775/eip.2022.003
|View full text |Cite
|
Sign up to set email alerts
|

Resource (in)efficiency in the EU: a case of plastic waste

Abstract: Motivation: Plastics are versatile materials with applications in numerous sectors. They contribute to effective resource protection during their usage phase but a great challenge is increasing amount of unmanaged plastic waste and its environmental impact. Meanwhile, plastic waste is a valuable raw material. Appropriate management reduces environmental pressure and brings economic benefits. The transition to circularity is a strategic objective of the EU but it involves numerous obstacles. This article deals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However, 80% of the companies agreed with the strategy involving the development and implementation of community awareness programs, aiming at supporting consumer attitude towards PW recovery and recycling. Awareness programs might target consumers and change their behavior regarding plastic use and disposal from linear to circular approach (Baran, 2022 ; Mehta et al, 2021 ). The plastic companies request immediate action from community members, rather than long-term cooperation of next generation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, 80% of the companies agreed with the strategy involving the development and implementation of community awareness programs, aiming at supporting consumer attitude towards PW recovery and recycling. Awareness programs might target consumers and change their behavior regarding plastic use and disposal from linear to circular approach (Baran, 2022 ; Mehta et al, 2021 ). The plastic companies request immediate action from community members, rather than long-term cooperation of next generation.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that higher rates of PW recovery and recycling are noticed in countries with landfill restrictions of recoverable and recyclable waste (PlasticsEurope, 2019 ) and those with the option of waste exportation to global markets such as China and India (Brems et al, 2012 ). In 2018, three European countries, namely, Switzerland, Austria, and Netherlands, had approached a zero landfilling target to achieve the circular economy of plastics (Baran, 2022 ; PlasticsEurope, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations